ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS (Studi Empiris pada Bank Badan Usaha Milik Negara Konvensional di Indonesia tahun 2012-2021) - Dimas Bagus Maulino Wibowo; Erma Setiawati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Operational Cost of Operating Income (BOPO), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), Company Size simultaneously or partially on Profitability (ROA) of Indonesian Conventional State-Owned Banks. The research population is Indonesian Convetional State-Owned Banks in 2012-2021 as many as 4 companies. The data analysis method used is multiple linear regression with a significance level of 0.005. The results showed that the Capital Adequacy Ratio (CAR, Operational Cost of Operating Income (BOPO, Net Interest Margin (NIM) had an effect on Profitability (ROA). Meanwhile, Loan to Deposit Ratio (LDR) and Company Size have no effect on Profitability (ROA).